2019
DOI: 10.1186/s12891-019-2672-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultraviolet photofunctionalization of titanium instrumentation in lumbar fusion: a non-randomized controlled trial

Abstract: Background Titanium instrumentations are widely used in orthopedics; the metal bonds with bone in a process called osseointegration. Over time, hydrocarbons adhere to the instrumentation, which weakens the bone-binding ability. Ultraviolet photofunctionalization enhances the bone-binding ability of instrumentation by reducing hydrocarbons. The process has been proven effective in dentistry, but its effects in orthopedics are unverified. We aimed to determine the effect of ultraviolet photofunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The literature search did not yield any randomized controlled clinical trials or prospective studies relevant to photofunctionalization other than seven (7) retrospective studies including a case series and case report. There was one (1) clinical trial on the photofunctionalization of titanium in orthopedic patients [91]. No direct data analysis was attempted, as clinical case reports do not provide an adequate source of evidence.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search did not yield any randomized controlled clinical trials or prospective studies relevant to photofunctionalization other than seven (7) retrospective studies including a case series and case report. There was one (1) clinical trial on the photofunctionalization of titanium in orthopedic patients [91]. No direct data analysis was attempted, as clinical case reports do not provide an adequate source of evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Additional hydrocarbons on titanium implant/instrument surfaces decreases bone-binding ability by aging [ 22 ]. However, PhF could promote osseointegration by reducing hydrocarbons [ 22 , 33 ].…”
Section: Preclinical Animal Studiesmentioning
confidence: 99%
“…After abstract review, there were two double-blind clinical trial studies, three prospective studies, four retrospective studies, and one case series in the present paper [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Furthermore, PhF applied in the spine surgery of 13 patients was included [ 22 ]. Except for some pre-clinical review papers on in vitro or animal studies, to my best knowledge, this paper is the first review focused on the clinical application of photofuctionalization [ 4 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photofunctionalization, which involves the use of ultraviolet (UV) treatment to modify titanium surfaces, has been shown to enhance bone-implant contact by changing the biological and biochemical properties of titanium [ [17] , [18] , [19] ]. It has been reported that titanium surfaces undergo a significant decrease in osseointegration capability after processing, which is associated with the disappearance of hydrophilicity [ 20 ], the progressive contamination of hydrocarbons [ 21 ], and the electrostatic status change on titanium surfaces over time [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is no UV irradiation equipment specifically for 3D-printed porous Ti6Al4V implants currently available. As UV photofunctionalization is effective on various titanium surfaces without altering their original topography or other morphological features, we specially designed a device targeted at the UV treatment of 3D-printed porous Ti6Al4V implants for osseointegration improvement [ [17] , [18] , [19] , [20] , [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%